Incidence of Retinopathy of Prematurity and Its Association with Oxygen Therapy in Preterm Low Birth Weight Babies - Pal, AK; Sur, Somen; Gupta, AK (Journal of Nepal Paediatric Society, 2016)
Introduction: The objectives of this study were to study the incidence and risk factors of retinopathy of prematurity (ROP) among preterm low birth weight babies and its association with oxygen therapy. Material and Methods: During one year study period, 50 neonates, who had fulfilled the inclusion criteria (born at gestational age ≤ 35 wks), were included in the present study. They were examined by indirect ophthalmoscopy by an ophthalmologist in NICU or ophthalmology outdoor. Staging of ROP was done according to the International classification. Data obtained from this study were entered in Microsoft Excel and subsequently analysed in SPSS version 20.0. Results: Among study population, 12 neonates (24%) showed evidence of retinopathy of prematurity, and Stage 2 ROP was most common (41.7%) within this group. Those neonates who had born ≤28 wks gestational age, showed more incidence (75%) of ROP. There was significant association between ROP and prematurity, low birth weight, mechanical ventilation, duration and concentration of oxygen therapy. Conclusion: Apart from prematurity and low birth weight, oxygen therapy also carries significant risk for ROP. Thus, judicious use of oxygen in premature babies can reduce incidence of ROP significantly. J Nepal Paediatr Soc 2015;35(3):247-252